Incidence and progression of myopia and associated factors in urban school children in Delhi: The North India Myopia Study (NIM Study) - Saxena, Rohit; Vashist, Praveen; Tandon, Radhika; Pandey, Ravindra M.; Bhardawaj, Amit; Gupta, Vivek; Menon, Vimala (PLOS ONE, 2017)
Aim To evaluate the incidence and progression of myopia and factors associated with progression of myopia in school going children in Delhi. Methods Prospective longitudinal study of 10,000 school children aged 5 to 15 years screened after an interval of 1 year to identify new myopes (Spherical Equivalent≤ -0.5D) and progression of myopia in previously diagnosed myopic children. Association between risk factors and progression was analyzed using adjusted odds ratio. Results Of the 9,616 children re-screened (97.3% coverage), annual incidence of myopia was 3.4%with mean dioptric change of -1.09 ± 0.55. There was a significant higher incidence of myopia in younger children compared to older children (P = 0.012) and among girls compared to boys (P = 0.002). Progression was observed in 49.2%children with mean dioptric change of -0.27 ± 0.42 diopters. The demographic and behavioral risk factors were analyzed for children with progression (n = 629) and adjusted odds ratio values were estimated. Hours of reading-writing/week (p<0.001), use of computers/ video games (P<0.001) and watching television (P = 0.048) were significant risk factors for progression of myopia. Outdoor activities / time spent outdoors> 2 hours in a day were protective with an inverse association with progression of myopia (P< 0.001). Conclusion Myopia is an important health issue in India and is associated with long hours of reading and screen time with use of computers and video games. An annual eye vision screening should be conducted, and outdoor activities be promoted to prevent the increase of myopia among school children.